Економічна динаміка України у 2024 році: ВВП, бюджетні показники та платіжний баланс - (:unkn) unknown (Підприємництво та інновації, 2024)
Economic changes in Ukraine in 2024 attract significant attention from academics, policymakers, and international experts. The current year is characterized by changes in macroeconomic indicators reflecting both internal economic processes and external influences. Examining aspects such as gross domestic product (GDP), budget performance, and balance of payments is key to understanding the current economic situation and predicting future trends. This article analyzes the dynamics of GDP, identifying the main factors that influenced its growth or decline. The work includes forecasts of the future development of the Ukrainian economy based on the data obtained. The study determines the impact of political and social factors on the country's economy. This information will be useful to government agencies, businesses and international organizations that are interested in the development of the Ukrainian economy. The article is aimed at a comprehensive analysis, assessment and forecasting of the main macroeconomic indicators of Ukraine in 2024. The article is aimed at increasing the understanding of the economic processes taking place in Ukraine. The relevance of the topic is due to the need to determine and assess the economic dynamics of Ukraine in the conditions of war, to predict changes in the structure of GDP, budget and balance of payments. The research methods of this topic were: statistical analysis, econometric analysis, regression analysis, content analysis, etc. Summing up, it is worth noting that based on our calculations, we predict that real GDP growth will slow down to about 3% this year. This is due to Russia's long-term active attacks on the country's energy system, the introduction of stabilization power outages, and the expectation of a smaller harvest compared to last year. At the end of the year, according to our calculations, we maintain the forecast of total budget revenues at the level of more than UAH 2.64 trillion (+50% to the plan), against UAH 2.67 trillion in 2023 (-1%). At the same time, the forecast of total state expenditures will also remain in the range of UAH 4.3-4.4 trillion, against UAH 4 trillion in 2023 (+7-10%). As mentioned above, the baseline forecast for financing the state budget for 2024 assumes its deficit at the level of UAH 1.71 trillion, or 23% of GDP (in 2023 – 21% of GDP). The total need for financing will amount to UAH 2.15 trillion ($53.7 billion). Thus, by the end of 2024, according to our calculations, external and internal public debt will increase to 97% of GDP. The practical value of the article lies in forecasting GDP, revenues and expenditures from the budget and balance of payments